MICROBIOLOGICAL PATTERN OF VENTILATOR ASSOCIATED PNEUMONIA - Ali, Shamshad; Waheed, Khalid; Iqbal, Zafar H (Journal of Ayub Medical College Abbottabad, 2015)
Background: Ventilator associated pneumonia (VAP) is an important and common complication of mechanically ventilated patients. It is the leading cause of morbidity and mortality in Intensive Care Units (ICU) worldwide. The aim of study was to determine the pattern of bacteria involved in VAP in intensive care unit of Jinnah hospital Lahore. Methods: It was descriptive case series study, conducted over a period of one year on mechanically ventilated 50 patients. American Thoracic Society (ATS) guidelines recommend quantitative/semi-quantitative culture of endotracheal aspirates (ETA) or bronchoscopic aspirates/washing from the infected lung segments for the diagnosis of VAP. Hence this study was conducted to identify the types of bacteria involved in VAP in our ICU. Patients enrolled were clinically and radiologically suspected VAP, admitted in the ICU of Jinnah Hospital/Allama Iqbal Medical College (AIMC) Lahore. Bronchial washings were taken with the help of Fiber optic bronchoscope. Wherever bronchoscopy was not possible, subglottic secretions were collected with the help of sterilized catheter and sucker. Collected samples were sent to the Pathology laboratory of AIMC for aerobic culture and sensitivity. Results: Major pathogenic bacteria isolated were Gram negative (74%). Among this group E. coli, Pseudomonas, Klebsiella and Acinetobacter were the commonest organisms. Gram positive bacteria were 20%, Staphylococcus aureus (MRSA) and Î²-haemolyticus streptococci were the major isolate. In 4% cases mixed growth and in 2% cases no growth was reported. Conclusion: Major pathogenic organisms of VAP in our ICU are Gram negative bacteria. The Bacteriological culture of endobroncheal aspirates is helpful in the diagnosis and management of VAP. Emperic antibiotic therapy for VAP should cover Gram negative organisms. Keywords: Ventilator Associated Pneumonia (VAP), Fiber Optical Bronchoscope (FOB), Intensive Care Unit (ICU), Endotracheal Aspirates (ETA), Culture and Sensitivity (C/S)